INSTRUCTIONAL MEDIA USED IN TEACHING ENGLISH - Silvi Aisyah; Acep Haryudin (PROJECT (Professional Journal of English Education), 2020)
This study investigates (1) the use of instructional media by teachers in teaching English to students. This research was conducted at a private elementary school in Cimahi, namely the Harapan Bangsa Creative Elementary School. To collect data, researchers used a case study approach with observation and interview techniques. The results showed that there are three types of learning media that are generally used by teachers, consisting of: (1) books (2) pictures and (3) videos. Each of these media is used in many different ways according to the needs of teaching and learning activities. In this case the teacher feels difficult to face challenges in the process of selecting and using instructional media due to lack of resources and enthusiasm from students so that teaching and learning activities become less effective and efficient. The solution used to solve the problem of learning media during the selection process is to utilize the media available at school. In the field observation process, the media that has been used by the teacher is a textbook. From the use of instructional media using textbooks only 75% of students are able to survive with these media. Keywords:         Instructional Media, English